2000
DOI: 10.1042/bst028a007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of signal transduction pathways by chemopreventive agents

Abstract: A disease such as cancer, where a number of alterations to normal cell function accumulate over time, presents several chernopreventive opportunities to inhibit, slow down or even reverse the process. Many of the crucial changes are induced by alterations to cell signalling pathways which regulate proliferation and apoptosis. As our knowledge of these complicated signalling networks improves, it is becoming clear that many molecules, both drugs and naturally occumng dietary constituents can interact beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Its ability to block tumor initiation has been rationalized in terms of upregulation of drug metabolizing enzymes, 27 whereas tumor suppression by I3C may be the consequence of modulation of pathways resulting in inhibition of cell proliferation or in compromised cell survival. 28,29 I3C has been shown to protect mice against hepatic damage induced by the hepatotoxicant carbon tetrachloride (CCl 4 ). 30 In this model, CCl 4 exerts its toxic effect via free radical species generated during reductive metabolism involving cytochrome P450.…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to block tumor initiation has been rationalized in terms of upregulation of drug metabolizing enzymes, 27 whereas tumor suppression by I3C may be the consequence of modulation of pathways resulting in inhibition of cell proliferation or in compromised cell survival. 28,29 I3C has been shown to protect mice against hepatic damage induced by the hepatotoxicant carbon tetrachloride (CCl 4 ). 30 In this model, CCl 4 exerts its toxic effect via free radical species generated during reductive metabolism involving cytochrome P450.…”
Section: Discussionmentioning
confidence: 99%
“…There are different groups of MAPK that are activated by different stimuli: among them ERK1 and ERK2 are activated by growth factor stimuli, whereas p38 kinases are activated by stress stimuli. Because treatment with low, physiological levels of Mn induces growth in astrocytes and astrocytoma cells [4,6] whereas treatment with higher, pathophysiological and toxicological levels of Mn induces stress in astrocytes [5], we have investigated the effects of Mn on both ERK1/2 and p38 proteins [7,8] in U87 astrocytoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and clinical studies suggest that indole-3-carbinol is a potential agent in blocking tumour initiation, oestrogen metabolism, inhibition of cell proliferation and induction of apoptosis [3,4,5,6,7]. So far, many studies have shown indole-3-carbinol is a bioactive component that plays an important anti-cancer role against breast [8], liver [9], prostate [10], lung and colon cancers [11,12].…”
Section: Introductionmentioning
confidence: 99%